PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 004 BANGSAL ACEH - Siti Rahmah Rahmah; Munjiatun '; Mahmud Alpusari Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract. The research problem is that the fourth grade students of SD Negeri 004 Bangsal Aceh got a low learning outcome on science. They only reached 53.82 on average for their daily score on science subject. This score was still far from the minimum score needed as the criteria of a successful learning (70). This happened because the learning process itself had a lot of weaknesses such as, teacher did not involve students much during the learning process, and the students did not get enough opportunities to be search information independently. Teacher failed to give attractive and acceptable learning experiences and to guide students to be active and critic in learning process. The formulation of the problem is “can the application of cooperative learning type TPS improve the science learning outcome of fourth grade students of SD Negeri 004 Bangsal Aceh?”. This research was an action research which had two cycles. In TPS, students got more chances to think individually, to find his/her learning pair, and to share their knowledge as an effort of peer learning. The improvement of learning outcome could be seen from the comparison of students’ test scores of pre test, post test I, post test II. The mean score of pre test was 53.82, and the mean score of post test I was 69.41 and the mean score of Post Test II was 79.41. These scores indicated that more than 85% of the students succeeded to pass the the successful criteria of learning process. TPS also succeeded to increase students’ participation during the learning process meeting by meeting. In Cycle I, The mean of students’ participation reached 82.50% and in cycle II, the mean of students’ participation increased into 92.50% and it was classified on very good level. In conclusion, Teacher succeeded to apply TPS well during the research and was able to make the students active and participative during the learning process. The students’ participation was very high so that it affects to students’ ability to absorb the lesson given. The increasing test results cycle by cycle indicated that TPS succeeded to increase students’ interest and learning outcome. Key Words    : Model, Cooperative Learning, Think Pair Share, TPS, Science Learning Outcome.